El acceso gratuito a la justicia y la obligación de rendir caución frente a la suspensión de ejecución del acto administrativo en materia tributaria - Fernando Misael, Inca Horna (2020)
Free access to justice is a transcendental right within our legal law, it must be respected and abided by before all authority, whether public or private, thus pursuing the purpose of the Constitution of the Republic of Ecuador that allows anyone who requires access the administration of justice can do it without having to make a payment of money so that it is intended to qualify a lawsuit and can continue with the hearing, nor is it intended to evade tax or money so it is not a matter of suspending the payment of the surety rather it is intended that an acquired right be respected by any citizen. Thus, article 324 of the General Organic Code of Processes is contradictory before the constitutional provision of free access to justice and effective judicial protection. To meet the objective, it will be determined through a critical, legal and doctrinal study if the payment of the surety to present the challenge of the Administrative Act in tax matters opposes the constitutional provision of free access to justice. From the results of the investigation, it will be established that the payment of the bond constitutes a violation of free access to justice, since the literal tenor of the norm established in the Constitution is not respected.